2021
DOI: 10.3389/fonc.2021.732058
|View full text |Cite
|
Sign up to set email alerts
|

TIMELESS Promotes Tumor Progression by Enhancing Macrophages Recruitment in Ovarian Cancer

Abstract: ObjectiveOvarian cancer (OV) is the most fatal and frequent type of gynecological malignancy worldwide. TIMELESS (TIM), as a circadian clock gene, has been found to be highly expressed and predictive of poor prognosis in various cancers. However, the function of TIM in OV is not known. This study was designed to investigate the biological functions and underlying mechanisms of TIM during OV progression.MethodsCell viability assay, cell migration assay, immunohistochemistry staining, qPCR analyses, and tumor xe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Pyroptosis is a newly discovered form of programmed cell death that is morphologically distinct from apoptosis and necrosis while releasing inflammatory mediators in the process (Wu et al, 2021). Pyroptosis is mediated by pore-forming proteins, such as the gasdermin family, of which gasdermin D (GSDMD) is a primary substrate for the caspase family (Li L. et al, 2021). After cleavage by activated caspases, the N-terminal fragment of GSDMD oligomerizes in the membrane to form pores, leading to pyroptosis (Lu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyroptosis is a newly discovered form of programmed cell death that is morphologically distinct from apoptosis and necrosis while releasing inflammatory mediators in the process (Wu et al, 2021). Pyroptosis is mediated by pore-forming proteins, such as the gasdermin family, of which gasdermin D (GSDMD) is a primary substrate for the caspase family (Li L. et al, 2021). After cleavage by activated caspases, the N-terminal fragment of GSDMD oligomerizes in the membrane to form pores, leading to pyroptosis (Lu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, high-throughput sequencing technologies and bioinformatics analysis have enabled the exploration of genetic alterations in osteosarcoma and provided an effective way to identify potentially beneficial markers and the most appropriate treatment strategies for other cancer types (Li M. et al, 2021;Na et al, 2021;Pan et al, 2021). According to Zhang et al (Xing et al, 2021), TIMELESS was the most significantly upregulated gene within the 16 clock-related genes by analyzing The Cancer Genome Atlas (TCGA) database and promoted cancer cell proliferation and migration via increasing macrophage infiltration in ovarian cancer. An analysis of the relationship between osteosarcoma development and KIF21B using bioinformatics analysis showed that knockdown of KIF21B inhibited cell proliferation and reduced tumor formation in vivo by modulating the PI3K/AKT pathway and that KIF21B was an independent prognostic factor in osteosarcoma patients (Ni et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This contrast could be due to the distinct pathophysiology of AML and ALL, where TIM could have different mechanisms in each subtype. For instance, a high expression of TIM has already been found in lung, cervical, and ovarian cancer cells, and is associated with its worse prognosis [ 160 , 162 , 163 , 164 ]. The upregulation of TIM could cause the greater inhibition of CLOCK , which would lead to a lack of Wee1 expression and, consequently, allow the leukemic cells to constantly replicate due to impaired Wee1 activity in the regulation of cell cycle checkpoints [ 165 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 52 PRGs were retrieved from the MSigDB Team (REACTOME_PYROPTOSIS) ( ) and prior reviews, which are shown in Table S1 ( 6 , 14 17 ). The “limma” package was used to determined DEPRGs by setting the cutoff criteria as p-value <0.05.…”
Section: Methodsmentioning
confidence: 99%